2017
DOI: 10.1039/c7fd00067g
|View full text |Cite
|
Sign up to set email alerts
|

Toward a reverse hierarchy of halogen bonding between bromine and iodine

Abstract: We compare here the halogen bond characteristics of bimolecular adducts involving either N-bromo- or N-iodosaccharin as strong halogen bond donors, with 4-picoline as a common XB acceptor. In the NBSac·Pic system, the bromine atom of NBSac is displaced toward the picoline, almost at a median position between the two nitrogen atoms, N and N', with NBr and BrN' distances at 2.073(6) and 2.098(6) Å respectively. This extreme situation contrasts with the analogous iodine derivative, NISac·Pic, where the N-I and IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(91 citation statements)
references
References 49 publications
4
87
0
Order By: Relevance
“…In the widely used QTAIM theory, [193] this kind of analysish as been deeplyd eveloped for 1ðr)t oc haracterize many aspects that this functione xhibits in atoms,m olecules and their interactions. [212,213] Thus, in the polyiodide chains of the crystal structure of tyrosinium polyiodide hydrate (Figure 10 b), iodines are distinguished from iodides by the type of CPs found in their interactions with surrounding atoms. Hence, the study of the topological critical points (CP) of r 2 1 r ðÞhas indicated that charge concentration (CC) and charge depletion (CD) sites found in the valence shell of atoms are drivingg eometric preferences of molecules in the solid state.…”
Section: Chemical Bonding Analysismentioning
confidence: 99%
“…In the widely used QTAIM theory, [193] this kind of analysish as been deeplyd eveloped for 1ðr)t oc haracterize many aspects that this functione xhibits in atoms,m olecules and their interactions. [212,213] Thus, in the polyiodide chains of the crystal structure of tyrosinium polyiodide hydrate (Figure 10 b), iodines are distinguished from iodides by the type of CPs found in their interactions with surrounding atoms. Hence, the study of the topological critical points (CP) of r 2 1 r ðÞhas indicated that charge concentration (CC) and charge depletion (CD) sites found in the valence shell of atoms are drivingg eometric preferences of molecules in the solid state.…”
Section: Chemical Bonding Analysismentioning
confidence: 99%
“…[8b] FourmiguØ et al have reported an almost symmetric XB between N-bromosaccharin and 4-methylpyridine with ac onsiderable charge transfer (0.27 e) to the acceptor. [9] On the other hand, Ř ezµč and de la Lande have determined that the charge transfer component, although present in XB-s,contributes only up to 10 %t othe overall energy even in strong XBs. [10] As the question of the charge transfer in XB has primarily been addressed from the computational point of view,w e have opted for experimental determination of charge density of asystem containing astrong, potentially partially covalent XB.Only ahandful of experimental charge density studies of halogen bonding have been published to date.…”
mentioning
confidence: 99%
“…, respectively, whereas one of the pillar of halogen bonding is that heavier halogens give stronger XBs, with numerous experimental and theoretical confirmations [2] and only one counterexample. [54] Obviously, ΔE int depends on all the interactions, therefore in this case the disentanglement of XB results to be particularly interesting.…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis of the homologues NCS and NIS, something unexpected emerges. The total interaction energy, with respect to relaxed fragments (Δ E tot ), is −26.2, −27.3, and −15.8 for [ SeU ] … [NIS], [ SeU ] … [NBS], and [ SeU ] … [NCS], respectively, whereas one of the pillar of halogen bonding is that heavier halogens give stronger XBs, with numerous experimental and theoretical confirmations and only one counter‐example . Obviously, Δ E int depends on all the interactions, therefore in this case the disentanglement of XB results to be particularly interesting.…”
Section: Resultsmentioning
confidence: 99%